2020
DOI: 10.1002/pbc.28421
|View full text |Cite
|
Sign up to set email alerts
|

Successful use of transarterial radioembolization with yttrium‐90 (TARE‐Y90) in two children with hepatoblastoma

Abstract: Primary malignant liver tumors are rare but all require surgical resection as part of therapy with curative intent. A minority of patients have resectable tumors at diagnosis. Chemotherapy has a therapeutic role in hepatoblastoma but only one‐third of patients have resectable disease at diagnosis. Two children with hepatoblastoma and suboptimal responses to initial chemotherapy received therapy with transarterial radioembolization utilizing yttrium‐90 (TARE‐Y90) and had significant response leading to resectio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 25 publications
1
12
0
Order By: Relevance
“…Transarterial chemo- or radio-embolisation: TACE or TARE is occasionally used to increase resectability in children who are not resectable and are not liver transplant candidates due to uncontrolled metastatic disease [ 12 , 13 ]. It has also been used to maintain tumour control for patients who have completed protocol systemic chemotherapy but for whom a donor organ for a needed transplant is not yet available.…”
Section: Other Surgical Considerationsmentioning
confidence: 99%
“…Transarterial chemo- or radio-embolisation: TACE or TARE is occasionally used to increase resectability in children who are not resectable and are not liver transplant candidates due to uncontrolled metastatic disease [ 12 , 13 ]. It has also been used to maintain tumour control for patients who have completed protocol systemic chemotherapy but for whom a donor organ for a needed transplant is not yet available.…”
Section: Other Surgical Considerationsmentioning
confidence: 99%
“…Most of these studies focus on TACE or TABE, reporting modest rates of tumor response and improved survival [ 32 , 33 , 34 , 35 ]. The only data available for TARE in hepatic sarcomas come from one multi-institutional retrospective study and case reports [ 19 , 36 , 37 ]. However, TARE is particularly appealing due to the lower incidence of post-embolization syndrome and hospital stays of only 2–3 h compared to TACE and other LDTs that often require hospitalization for 1–3 days [ 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…These techniques are already used as bridge therapy for adult patients and, though still not widespread for pediatric ones, should be considered. A retrospective study showed no differences in safety and in the response rate to RA in relapsed HB compared with surgery, as well as an alternative to tumors that did not respond to neoadjuvant therapy [18][19][20][21][22] .…”
Section: Rev Col Bras Cir 49:e20223273mentioning
confidence: 99%